1987
DOI: 10.1055/s-2007-1011836
|View full text |Cite
|
Sign up to set email alerts
|

Flight Effects on Plasma Glucose, Lactate, Catecholamines and Corticosterone in Homing Pigeons

Abstract: Significant increase in the circulating levels of glucose, lactate, adrenaline (A) and noradrenaline (NA) was observed in homing pigeons after a flight of 48 km, lasting 60-80 min. There was, however, no change in plasma corticosterone concentrations. The increase in lactate has been attributed mainly to the activity of the white glycolytic fibres in the flight muscles. The increase in A and NA indicated increased sympathetic activity. It is suggested that the flight-induced increase in A stimulated the releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

1989
1989
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…Environmental conditions such as temperature, wind and light may also act as stressors. In a recent study with homing pigeons, it was observed that during moderate natural free flight (60-80 min duration), there was no change in plasma levels of corticosterone (Viswanathan, John, George and Etches 1987), contrary to the nearly two-fold increase observed in anesthetized pigeons whose breast muscles were exercised by electrical stimulation (Pilo, John, George and Etches 1984). Working with homing pigeons, Haase, Rees and Harvey (1986) reported increases in circulating levels of corticosterone after free flights of less than one min and also of 315-561 min durations covering distances of 100 m and 115-557 km respectively.…”
Section: Introductionmentioning
confidence: 87%
See 1 more Smart Citation
“…Environmental conditions such as temperature, wind and light may also act as stressors. In a recent study with homing pigeons, it was observed that during moderate natural free flight (60-80 min duration), there was no change in plasma levels of corticosterone (Viswanathan, John, George and Etches 1987), contrary to the nearly two-fold increase observed in anesthetized pigeons whose breast muscles were exercised by electrical stimulation (Pilo, John, George and Etches 1984). Working with homing pigeons, Haase, Rees and Harvey (1986) reported increases in circulating levels of corticosterone after free flights of less than one min and also of 315-561 min durations covering distances of 100 m and 115-557 km respectively.…”
Section: Introductionmentioning
confidence: 87%
“…Working with homing pigeons, Haase, Rees and Harvey (1986) reported increases in circulating levels of corticosterone after free flights of less than one min and also of 315-561 min durations covering distances of 100 m and 115-557 km respectively. The two studies with homing pigeons suggest that plasma corticosterone level could rise initially and level off during moderate short-term flight but could again increase significantly with longer and more exhausting flight (Viswanathan et al 1987).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the connections between flight and glucocorticoid concentrations are a bit ambiguous. Studies in pigeons suggest a graduated relationship between flight length and corticosterone concentration (Haase et al, 1986;Viswanathan et al, 1987), which would mirror the relationship between exercise intensity and cortisol concentration in humans (Pedersen and Hoffman-Goetz, 2000). Yet other studies suggest that long flights have no effect on corticosterone concentrations (Hasselquist et al, 2007).…”
Section: Effects Of Flightmentioning
confidence: 97%
“…It has also been shown that a flight of this duration and magnitude did not produce any increase in plasma levels of corticosterone in homing pigeons [21], How ever, it should be mentioned that MT in birds and oxytocin in mammals may not be identi cal in function and that there is no evidence to suggest that MT is a stress hormone in birds.…”
Section: Discussionmentioning
confidence: 95%
“…Trained homing pigeons are an excellent experimental material for studies on the ef fects of natural free flight on the physiology of bird flight. Recent studies with homing pi geons have thrown considerable new light on the effects of flight on circulating levels of metabolites and certain hormones involved in metabolic regulation [21][22][23], In the present study, we have investigated possible changes in circulating levels of AVT and MT as a result of flight in homing pigeons.…”
Section: Introductionmentioning
confidence: 99%